Assessment of serum electrolytes, nutritional status, and oxygen saturation among athletic Senior High School students - Insyirah Muhammad; Herlina Dimiati; Zafrullah Khany Jasa (AcTion: Aceh Nutrition Journal, 2025)
Adolescent athletes have a higher risk of dehydration than adult athletes do. This increased risk results from the greater absorption of environmental heat and heightened body heat, which affects electrolyte balance and oxygen saturation. This study aimed to analyze electrolyte values and oxygen saturation in students at SMA Keberbakatan Aceh in 2024 using an observational analytical approach with a cross-sectional design. A total of 43 respondents were selected for this study. The intensity of physical exercise was assessed using the International Physical Activity Questionnaire (IPAQ) score,  of which two respondents had hyponatremia, 40 had normal sodium levels, and one respondent had hypernatremia related to the intensity of physical exercise (p= 0,381). Potassium levels were not significantly affected, as all 43 respondents had normal potassium levels (p= 0,740). Regarding chloride levels, one respondent had hypochloremia, 40 had normal levels, and two had hyperchloremia. While previous results showed no effect, exercise intensity was found to have a significant influence on respondents’ nutritional status (p= 0,034). All respondents maintained levels within normal limits in the assessment of oxygen saturation. Conclusion: Physical exercise intensity had no significant effect on serum electrolytes or oxygen saturation levels. However, a significant relationship was observed between the physical exercise intensity and nutritional status.